Transition metal dichalcogenide micromotors with programmable photophoretic swarming motion. Issue 3 (19th December 2022) - de la Asunción-Nadal, Víctor; Rojas, Daniel; Jurado-Sánchez, Beatriz; Escarpa, Alberto
Abstract : Herein we report the light-triggered photophoretic motion of WS2 micromotors. Abstract : Herein we report the light-triggered photophoretic motion of WS2 micromotors. The micromotors are prepared by liquid-phase exfoliation of pristine WS2 in water, resulting in a layered material with high photoconversion capability. Under electromagnetic irradiation in the UV or VIS range, the micromotors exhibit a positive photophoretic motion and swarming-like schooling behavior. The light-induced heating of the prepared micromotors is studied and computational fluid dynamics simulations are considered to characterize the photophoretic propulsion mechanism. The novel micromotors described here are capable of performing a collective motion without the need for surfactants, fuels, or other reagents, reaching velocities of up to 6000 μm s −1 . To date, this represents the fastest light-driven micromotor platform, paving the way for novel cutting-edge applications.